Spillover effects of drug safety warnings on health behavior - N. Meltem Daysal; Chiara Orsini (Institute for the Study of Labor (IZA), 2012)
We examine the impact of new medical information on drug safety on preventive health behavior. We exploit the release of the findings of the Women's Health Initiative Study (WHIS) - the largest randomized controlled trial of women's health - which demonstrated in 2002 that long-term Hormone Replacement Therapy increases the risk of heart attacks, stroke, blood clots and breast cancer among healthy post-menopausal women. Because hormone replacement is a therapy exclusive to women, we estimate the spillover effects of the WHIS findings on health behavior by means of a difference-in-differences methodology using men of similar ages as the control group. Using data from the Behavioral Risk Factor Surveillance System for 1998-2007, we find statistically significant small negative spillovers on post-menopausal women's likelihood of having an annual checkup and choice of a healthy diet, as proxied by daily fruit consumption. Our results also indicate that the observed spillover effects of drug safety on health behavior were entirely driven by the less educated. These findings suggest that policies aimed at raising awareness on the safety of medications may have unintended spillover effects on health behavior and that these spillovers may contribute to the existing health disparities by education.
urn:nbn:de:101:1-201206146980
Keywords: I10; I12; I14; I18; 330; spillovers; preventive behavior; health disparities; health production; Pharmazeutisches Produkt; Produktinformation; Gesundheitsrisiko; Gesundheitsvorsorge; Frauen; USA